Wabah dalam Perspektif Kristen dan Islam (Studi Alkitab dan Al Qur’an sebagai Kitab Suci) - Mercusuarridha, Mercusuarridha; HS, Moh. Nuh (Inklusiva: Jurnal Studi Agama-Agama, 2024)
The phenomenon of the Covid-19 disease outbreak raises various speculations and questions, especially how the correlation between the disease outbreak and religion. This research is a literature research that aims to explain the conception of the plague in the perspective of Christianity and Islam through the study of the Bible and the Qur'an, with a descriptive analysis method. The results of this research, first, the plague is a form of punishment from God. Second, the plague is a "tool" to test faith. Third, the plague is a sign of God's power. There are two principles of Christian faith in the face of suffering. The first principle, Christian faith is not passive faith, but active faith which means facing suffering as part of life. The second principle is that faith in Christ is an optimistic faith, not pessimism that breeds despair. In the school of Islamic theology, there are at least three groups. First, the Jabariyyah group, surrendered completely to the destiny of Allah. Second, the qadariyyah group, which believes in one's own strength without involving Allah. Third, Ahlus Sunnah wal Jama'ah, which is a group that balances effort and tawakkal.